Glucarpidase for Treating Adults with Delayed Methotrexate Elimination Due to Impaired Renal Function: An Economic Simulation Analysis - Kala J; Nelson R; Drudge C; Zhou A; Ward S; Bourque M (Dove Medical Press, 2023)
Jaya Kala,1,* Rebecca Nelson,2,* Christopher Drudge,3 Allen Zhou,3 Suzanne Ward,4 Megan Bourque3 1University of Texas Health Science Center, Houston, TX, USA; 2Moffitt Cancer Center and Research Institute, Tampa, FL, USA; 3Value and Evidence, EVERSANA, Burlington, ON, Canada; 4BTG International Inc, West Conshohocken, PA, USA*These authors contributed equally to this workCorrespondence: Christopher Drudge, Value and Evidence, EVERSANA, 204-3228 South Service Road, Burlington, ON, L7N 3H8, Canada, Tel +1 905 637 6231, Fax +1 905 637 5014, Email chris.drudge@eversana.comBackground: Glucarpidase is indicated for treating delayed methotrexate (MTX) elimination due to impaired renal function. Although glucarpidase is capable of rapidly eliminating MTX independent of renal clearance, its cost can be perceived as a barrier to use. However, no published economic analyses have evaluated glucarpidase relative to comparable treatments.Purpose: To assess the economic value of glucarpidase for treating adult patients in the United States (US) who experience delayed MTX elimination due to impaired renal function.Methods: A decision tree model was developed to assess the economic value of glucarpidase. The short-term inpatient management of patients as well as long-term survival were simulated. Costs associated with the use of glucarpidase were compared against other methods for treating delayed MTX elimination due to impaired renal function under two scenarios: current practice (ie, mix of timely/delayed use of glucarpidase, hemodialysis, or supportive care [SC] alone) as compared with proposed practice (ie, timely glucarpidase administration within 60 hours for all eligible patients). Hypothetical practical scenarios for US institutions were also considered.Results: For adult patients with delayed MTX elimination, proposed practice as compared to current practice was associated with an increased cost of $20,024 per patient, not considering any incremental reimbursement associated with glucarpidase administration. Importantly, early treatment with glucarpidase, within 60 hours, was shown to be less expensive per patient than delayed glucarpidase treatment or treating with hemodialysis, but more expensive than SC alone. However, proposed practice was associated with multiple clinical benefits, including shorter hospital length of stay. For hypothetical practical scenarios, minimal shifts in treatment patterns had minimal cost impacts.Conclusion: Treatment of all eligible patients with glucarpidase within 60 hours was associated with an increased cost per patient (relative to current practice) but substantial improvements in clinical outcomes. Timely glucarpidase use was less expensive than delayed glucarpidase or hemodialysis.Keywords: chemotherapy, toxicity, costs, outcomes